Clinical use of CAR T-cells in treating acute lymphoblastic leukemia. (April 2023) - Korkmaz, Serdal
Abstract: Chimeric antigen receptor (CAR) T-cell therapy has transformed the treatment landscape for adult patients with relapsed or refractory B-cell acute lymphoblastic leukemia (R/R B-ALL). However CAR T-cell therapy of R/R T-ALL has unique challenges, such as the lack of specific tumor antigens, cell fratricide and T cell aplasia, in comparison with that of R/R B-ALL. Despite promising therapeutic outcomes in R/R B-ALL, application of this therapy is limited by high relapse rates and immunological toxicities. Recent studies suggest patients who underwent allogeneic hematopoietic stem cell transplantation post-CAR T-cell therapy would achieve durable remission and better survival, but this remains controversial. Herein, I briefly review published data on the clinical use of CAR T-cells in treating ALL.